Overview of the biodiversity and geographic distribution of aloricate oligotrich ciliates (Protozoa, Ciliophora, Spirotrichea) in coastal waters of southern China. Issue 8 (17th November 2019) - Liu, Weiwei; Zhang, Kexin; Chen, Changzhi; Li, Jiqiu; Tan, Yehui; Warren, Alan; Lin, Xiaofeng; Song, Weibo
Abstract : Aloricate oligotrich ciliates are important components of marine microplankton. This paper summarizes the results of several biodiversity and faunal studies on this group in typical coastal habitats of southern China that were carried out from 2006 to 2016. The main findings are as follows: (1) a total of 39 species belonging to 17 genera, seven families and four orders of aloricate oligotrich ( s. l. ) ciliates were identified from coastal waters of Zhanjiang, Guangzhou, Shenzhen, Huizhou, and Hong Kong; among these 16 species, four genera, one family and one order were new to science; (2) the order Oligotrichida represents the most abundant taxon with highest species richness and its members are widely distributed in all coastal habitats; the family Strombidiidae and the genus Strombidium comprise the highest proportion of all oligotrichs at family and genus levels, respectively; (3) based on the results of our taxonomic investigations, the biodiversity of oligotrichs in five typical habitats are compared; mangrove wetland possessing the highest species richness of oligotrich ciliates represents a biodiversity hotspot habitat in the southern coast of China; (4) morphologies of 10 poorly known species, namely Pelagohalteria cirrifera, Strombidium conicum, Spirostrombidium schizostomum, Parallelostrombidium paralatum, Omegastrombidium elegans, Varistrombidium kielum, Spirotontonia turbinata, Pelagostrobilidium simile, Strombidinopsis batos, and Strombidinopsis cheshiri are redescribed based on living and protargol-stained specimens, and some new characters are analysed. Improved diagnoses of Strombidium conicum and Strombidinopsis batos are supplied.